Clinical and Genetic Analysis of Multiple Osteochondromas in a Cohort of Argentine Patients - Caino, Silvia (2022)
Multiple Osteochondromatosis (MO, MIM 133700 & 133701), an autosomal dominant O-glycosylation disorder (EXT1/EXT2-CDG), can be associated with a reduction in skeletal growth, bony deformity, restricted joint motion, shortened stature and pathogenic variants in two tumor suppressor genes, EXT1 and EXT2. In this work, we report a cross-sectional study including 35 index patients and 20 affected family members. Clinical phenotyping of all 55 affected cases was obtained, but genetic studies were performed only in 35 indexes. Of these, a total of 40% (n = 14) had a family history of MO. Clinical severity scores were class I in 34% (n:18), class II in 24.5% (n:13) and class III in 41.5% (n:22). Pathogenic variants were identified in 83% (29/35) probands. We detected 18 (62%) in EXT1 and 11 (38%) in EXT2. Patients with EXT1 variants showed a height z-score of 1.03 SD lower than those with EXT2 variants and greater clinical severity (II–III vs. I). Interestingly, three patients showed intellectual impairment, two patients showed a dual diagnosis, one Turner Syndrome and one hypochondroplasia. This study improves knowledge of MO, reporting new pathogenic variants and forwarding the worldwide collaboration necessary to promote the inclusion of patients into future biologically based therapeutics.